Processo de conscientização do futuro professor de língua inglesa sobre as especificidades de se aprender inglês para ensinar - Emidio, Denise Elaine (2007)
This dissertation presents the results of an investigation about the consciousness development of pre-service EFL teachers, throughout their first year, that learning the language as prospective teachers is different from learning for general purposes (in language courses, for example). We have analyzed classes in an EFL teacher Education program that presents theory in the study of the target language (Content-based instruction - CBI) since pre-service teacher first year at the university. These undergraduate students carry (mis)beliefs, which cause them disappointment and resistance against the syllabus. However, in the end of the first year it is possible to notice the beginning of a consciousness process in some participants. Our study shows that the CBI is appropriate for EFL teacher education. Nevertheless there should be a smoother process of consciousness raising of students that they are in a different position than that of mere language learners, so that they can notice this new role by themselves